2015
DOI: 10.1186/2052-1847-7-3
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility and effectiveness of high-intensity boxing training versus moderate-intensity brisk walking in adults with abdominal obesity: a pilot study

Abstract: BackgroundHigh-intensity interval training (HIIT) performed on exercise cycle or treadmill is considered safe and often more beneficial for fat loss and cardiometabolic health than moderate-intensity continuous training (MICT). The aim of this pilot study was to assess the feasibility and effectiveness of a 12-week boxing training (HIIT) intervention compared with an equivalent dose of brisk walking (MICT) in obese adults.MethodsMen and women with abdominal obesity and body mass index >25 kg/m2 were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(126 citation statements)
references
References 40 publications
2
92
0
7
Order By: Relevance
“…Only one study71 employed both HIIT and SIT interventions, and one study included two HIIT interventions 86. Of the 41 studies, 20 used cycling,24 55 57 58 69 70 72 73 75 78–81 83 84 87–90 93 16 used walking/jogging/running,54 56 59–67 71 77 82 91 92 1 used a synchronous arm and leg air-braked ergometer,85 1 offered a choice between the two (cycle ergometer or walking/running) depending on orthopaedic limitations,86 1 used swimming,74 1 used boxing drills for the HIIT protocol and walking for MOD,76 and 1 used a rower ergometer 68. Intervention duration ranged from 468 73 75 81 to 16 weeks,86 87 with 12 weeks being the most common (~44%; n=18)54 56 57 59 63 64 66 67 70 71 76 80 82–84 89 92 93 (online supplementary table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study71 employed both HIIT and SIT interventions, and one study included two HIIT interventions 86. Of the 41 studies, 20 used cycling,24 55 57 58 69 70 72 73 75 78–81 83 84 87–90 93 16 used walking/jogging/running,54 56 59–67 71 77 82 91 92 1 used a synchronous arm and leg air-braked ergometer,85 1 offered a choice between the two (cycle ergometer or walking/running) depending on orthopaedic limitations,86 1 used swimming,74 1 used boxing drills for the HIIT protocol and walking for MOD,76 and 1 used a rower ergometer 68. Intervention duration ranged from 468 73 75 81 to 16 weeks,86 87 with 12 weeks being the most common (~44%; n=18)54 56 57 59 63 64 66 67 70 71 76 80 82–84 89 92 93 (online supplementary table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The intensity of effort for HIIT protocols was prescribed by the percentage of i true0V˙ O 2 max66 67 77 or i true0V˙ O 2 peak,58 percentage of true0V˙ O 2 max55 63 73 or true0V˙ O 2 peak,70 percentage of HRmax54 56 59 71 78 87 90 92 93 or peak heart rate (HRpeak),64 65 81 82 85 86 rating of perceived exertion,76 HR corresponding to 20% above the HR at ventilatory threshold,57 and 90% of 4 min maximal power 68. The intensity of effort in most SIT protocols (n=13) was prescribed by ‘all-out’ efforts,24 60–62 69 71 72 74 83 84 88 89 91 percentage of i true0V˙ O 2 peak,80 percentage of maximal power output75 and percentage of anaerobic power 79…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with previous studies examining the feasibility of novel exercise activities for a variety of at-risk populations, feasibility of the home-based bimodal prehabilitation program will be determined by participation rate and reasons for non-participation, the registration of the number and severity of adverse events, adherence to the program, and drop-out rate and reasons for drop-out. [33][34][35] Adverse events will be recorded by the community physical therapist. Data concerning training intensity and duration from each interval and endurance training session will be displayed at the cycle ergometer following a training session, and recorded by the physical therapist or by the patient in case of an unsupervised training session.…”
Section: Feasibility Of the Prehabilitation Programmentioning
confidence: 99%
“…Kafri et al(2014) carried out an additional comparison between sports AVGs and walking at a comfortable pace. Finally, one study compared virtual boxing with real heavy bag training (Mat Rosly et al, 2017 Regarding training loads, five studies reported on exercise intensity (Cheema et al, 2015;Gaffurini et al, 2013;Hurkmans et al, 2011Hurkmans et al, , 2010Mat Rosly et al, 2017) and four on training progress and the criteria used to plan the sessions (Abdulsatar et al, 2013;Combs et al, 2011;Mat Rosly et al, 2017;Park et al, 2017). Seven studies provided information about the location in which boxing et al, Combs et al, 2011;Hurkmans et al, 2011Hurkmans et al, , 2010Mat Rosly et al, 2017;Park et al, 2017).…”
Section: Characteristics Of the Interventionsmentioning
confidence: 99%